Perceptions of rural high school teachers ‐ on the frontline of youth suicide. (29th June 2022) - Bowman, Siann; McKinstry, Carol; Howie, Linsey; Hepworth, Graham; McGorry, Patrick
Abstract: Objective: This study aimed to investigate the perceptions and beliefs of rural high school teachers about student suicide completion in their school and their perceived self‐efficacy in identification of suicidality in students (suicidal ideation, plans and behaviours). Design: A cross‐sectional survey methodology. Setting: Gippsland and the Loddon Mallee regions of Victoria, Australia. Participants: Rural high school teachers. Outcome Measure: A survey that aimed to obtain participants' perceptions and self‐reports about students who had died by suicide in their school within the last 5 years, their perceived self‐efficacy in identifying suicidal students and barriers to helping students at risk. Results: Two hundred and seventy‐seven rural high school teachers participated and 86% reported that a student from their school had died by suicide within the last 5 years. Sixty‐five per cent believed that more than one student had died by suicide and 70% perceived they were currently aware of students experiencing suicidality in their class. Receiving professional development about suicide and obtaining help from mental health clinicians predicted perceived self‐efficacy in identification of suicidality in students. Participants perceived the barriers to help students at risk included insufficient numbers of school‐based mental health professionals and community mental health services. Conclusions: Many rural high school teachers perceive they are at the front line of the youth suicide crisis due to unmet service need in youth mental ill health. Increased access to effective services immediately after teachers become aware of suicidality may assist in reducing youth suicide in rural areas.